An equation of state for London dispersion interaction with thermodynamic inconsistent terms - Marwan Al-Raeei (Results in Chemistry, 2022)
One of the most important potential in the physical systems is London dispersion potential which is very significant in a lot of systems, for instance, the soft materials systems, some gaseous systems and some liquid systems. In the following work, we use the principles of the integral equations theory for derivation of an equation of state for the London dispersion potential where we apply the mean-spherical-approximation for this purpose with thermodynamic inconsistent principle. We take into account the virial expansion formula and the compressibility formula of the pressure. We found that the pressure is function to the temperature of the described systems and fractional volume of the components in the systems, in addition to the first ionization energy and the polarizablitiy of the components in the systems. We believe that the formula of the equation of state for London dispersion interaction which we derive in this study is general and suitable for compositions which interact via London dispersion effects.